Sorption purification of mine ralized groundwaters from uranium compounds by pillared clays - Kovalchuk, I.A.; Pylypenko, I.V.; Kornilovych, B.Yu.; Bashchak, O.E. (Reports of the National Academy of Sciences of Ukraine, 2019)
The removal of uranium (VI) from mineralized groundwaters by the adsorption onto pillared-bentonites is investigated. Various complexes of U(VI) in mineralized waters are examined. It has been shown that, in mineralized groundwaters, anionic carbonate complexes of U(VI) are selectively removed by samples of pillaredbentonite. Adsorption isotherms are obtained at pH 7.2 and an uranium concentration of 10—100 mg/l. The order of extracting anionic forms of uranium by pillared-bentonites is Ti > Fe > Zr> Al indicating that the Ti-pillared-bentonite form is the most effective in the removal of U(VI) from mineralized groundwaters. The uranium sorption data are fitted by the Langmuir and Freundlich equilibrium models to obtain the characteristic parameters of each model. According to the evaluation using the Langmuir model, the maximum sorption capacity of uranium (VI) ions onto Ti-pillared-bentonite is 36.57 mg/g under the ratio of solid to liquid 500 in 1 h. The results suggest that pillared-bentonites are suitable materials for the preconcentration and solidification of uranium (VI) species from mineralized groundwaters.